Taking Your iPhone 4 to the Max - Sande, Steve; Sadun, Erica; Andres, Clay.; Welsh, Tom.; Anglin, Steve; Beckner, Mark.; Buckingham, Ewan.; Cornell, Gary.; Gennick, Jonathan; Hassell, Jonathan; Lowman, Michelle; Moodie, Matthew; et al. (Berkeley, CA : Apress, 2010)
Unleash your iPhone and take it to the limit using powerful tips and techniques from tech consultant Steve Sande and gadget hacker Erica Sadun. Fast and fun to read, Taking Your iPhone 4 to the Max shows you how to get the most out of Apple's iPhone 4. You'll find all the best undocumented tricks as well as the most efficient and enjoyable introduction to the iPhone available. Starting with an introduction to iPhone basics, you'll quickly move on to discover the iPhone's hidden potential, like how to connect to a TV, use Voice Control, have video chats with FaceTime, and call friends overseas with low-cost VoIP. From the unified email inbox and surfing the Web with Mobile Safari, exploring the world of social networking, using the multitasking capabilities of iOS 4, taking and editing photos, shopping for apps, media, and books, or just managing phone callsPQZ-21723you'll find it all in this book. You'll even learn tips on where to get the best iPhone accessories. Get ready to take iPhone 4 to the max!
Selecting, Buying, and Activating Your iPhone -- Interacting with Your New iPhone -- Placing Calls with iPhone -- iPhone Messaging and Social Networking -- iPhone E-mail -- Syncing Your iPhone with iTunes -- It$1 (Bs Also an iPod -- iPhone Photos and Video -- Browsing with Safari -- The Shopping Mall in Your iPhone -- Google Maps and Other Apps.s
Keywords: Computer science; Computer Science; Computer Science, general